Mesenchymal stem cell‐derived exosomes mitigate amyloid β‐induced retinal toxicity: Insights from rat model and cellular studies - Amanda Qarawani; Efrat Naaman; Rony Ben‐Zvi Elimelech; Michal Harel; Shahaf Sigal‐Dror; Tali Ben‐Zur; Tamar Ziv; Daniel Offen; Shiri Zayit‐Soudry (Journal of Extracellular Biology)
Abstract Amyloid β (Aβ) has emerged as a pathophysiological driver in age‐related macular degeneration (AMD), emphasizing its significance in the aetiology of this prevalent sight‐threatening condition. The multifaceted nature of AMD pathophysiology, presumably involving diverse retinal cascades, corresponds with the complexity of Aβ‐induced retinopathy. Therefore, targeting a broad array of pathogenic processes holds promise for therapeutic intervention in AMD‐associated retinal pathology. This study investigates the potential of exosomes derived from adipose tissue mesenchymal stem cells (AT‐MSC‐Exosomes) in alleviating Aβ‐induced retinotoxicity. Through intravitreal injections in wild‐type rats and RPE‐like cell culture experiments, we examined the protective effects of AT‐MSC‐Exosomes against Aβ42 retinotoxicity. Our findings reveal that pre‐treatment with AT‐MSC‐Exosomes enabled nearly‐intact retinal function in vivo and maintained retinal cell viability in vitro, evidenced by longitudinal electroretinography (ERG) and XTT proliferation assays, respectively. Fluorescent labelling demonstrated increased migration of AT‐MSC‐Exosomes towards retinal cells under conditions of amyloid‐related toxicity. Proteomic analysis indicated a decrease in the retinal levels of heat‐shock proteins activated by pathogenic Aβ fibrils following AT‐MSC‐Exosome treatment. Similarly, immunostaining highlighted the modulation of α‐crystallin expression in retinal astrocytes by AT‐MSC‐Exosomes. These results suggest the potential therapeutic relevance of AT‐MSC‐Exosomes in Aβ‐related retinal pathology, offering a promising avenue for future AMD treatment strategies.